Usability Evaluation Of Social Security For Workers Applications In Public Institutions - Afrizon, Asra; Hadi Putra, Panca (The Indonesian Journal of Computer Science, 2023)
Workforce social security application services are owned by the Indonesian government and held by the Social Security Administering Body on Employment. Initially, the application only provided social security programs, membership, and benefits information. In September 2021, the application was transformed by including transactions for claim redemption. User reviews of the application gave ratings of 1.5 and 4.4, respectively meanwhile complaints and requests for information in 2022 were the second highest, accounting for 65% and 5%, respectively. Through analysis of user reviews and complaints, it has been determined that users encounter multiple constraints when utilizing applications concerning accessibility, information, authentication, procedures, and comprehension of usage. The research method involves a quantitative approach using a user experience questionnaire and usability testing methods through task scenarios. Followed by a qualitative approach using a post-test interview to conduct deep dive into user problems and expectations. This study aims to evaluate the application's usability and provide recommendations for improvement. Based on the analysis from UEQ, the application get an average value positive, and the benchmark result is above average. In contrast, the novelty gets neutral, and the benchmark result is below average, reviewed as conventional, slow, less valuable, challenging to learn, and monotonous. The test task scenario described effectivity of application. Meanwhile, time-based efficiency is 0,04 goals/second, which can be interpreted as high speed. Task scenario finding explains 30 problems in which three tasks are prioritized. Post-test interviews explained user need for frequently accessed features, difficulty to use, and usage limitations. The recommendations aimed to adjust the interface and functionality to meet user needs, providing a satisfying experience and shortening the self-service process.